2009
DOI: 10.1523/jneurosci.0511-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry of Perisaccadic Visual Perception

Abstract: Our ability to explore our surroundings requires a combination of high-resolution vision and frequent rotations of the visual axis toward objects of interest. Such gaze shifts are themselves a source of powerful retinal stimulation, and so the visual system appears to have evolved mechanisms to maintain perceptual stability during movements of the eyes in space. The mechanisms underlying this perceptual stability can be probed in the laboratory by briefly presenting a stimulus around the time of a saccadic eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 81 publications
4
34
1
Order By: Relevance
“…By assuming a certain qualitative ratio of magnification along the rays and circles of constant eccentricity [103 -105], the model is able to explain not only the mislocalization of spatially extended bars (figure 3b), but also the asymmetric two-dimensional spatial pattern of compression (figure 3c). The notion of cortical magnification as a crucial property to model the observed mislocalization has recently also been demonstrated by Richard et al [101], who showed that the distance between stimulus and target in cortical space, as opposed to visual space, predicts the strength of the mislocalization. Because the visual responses of neurons in the spatial re-entry model are modulated by oculomotor feedback signals, the receptive fields in the model undergo dynamic changes before and during the saccade (figure 3d ).…”
Section: Theories and Computational Models Of Peri-and Trans-saccadicmentioning
confidence: 76%
“…By assuming a certain qualitative ratio of magnification along the rays and circles of constant eccentricity [103 -105], the model is able to explain not only the mislocalization of spatially extended bars (figure 3b), but also the asymmetric two-dimensional spatial pattern of compression (figure 3c). The notion of cortical magnification as a crucial property to model the observed mislocalization has recently also been demonstrated by Richard et al [101], who showed that the distance between stimulus and target in cortical space, as opposed to visual space, predicts the strength of the mislocalization. Because the visual responses of neurons in the spatial re-entry model are modulated by oculomotor feedback signals, the receptive fields in the model undergo dynamic changes before and during the saccade (figure 3d ).…”
Section: Theories and Computational Models Of Peri-and Trans-saccadicmentioning
confidence: 76%
“…Kaiser and Lappe (2004) showed that the magnitude of the mislocalization increased with saccade amplitude when they flashed a dot at various positions around the onset of 12-to 24-saccades. This effect was recently replicated by Richard, Churan, Guitton, and Pack (2009) with 14-to 30-saccades but modulated by the flashed stimulus position.…”
Section: Introductionmentioning
confidence: 74%
“…However, this alternative does not seem to fit with the results of Morrone et al (1997) who found a clear compression pattern for 2.5-saccades when bars were flashed at a maximal distance of 3.75-. Richard et al (2009) systematically tested the influence of both saccade amplitude and bar position for saccades of 14-, 20-, and 30-and showed that the influence of saccade amplitude on compression strength could be modulated by bar position. More precisely, for 20-and 30-saccades, they showed different patterns of compression depending on whether the bar's absolute position (i.e., relative to fixation cross) or relative position (i.e., relative to saccade target) was held constant.…”
Section: Introductionmentioning
confidence: 99%
“…From these considerations it follows that brief pulses of wide-field motion are processed by neurons in the visual system tens of thousands of times per day. Previous work has provided support for the existence of specialized mechanisms that suppress the perceptual effects of such motion stimuli (Murakami & Cavanagh, 1998), and we have recently begun investigating these mechanisms with stimuli similar to those used in the current experiments (Richard, Churan, Guitton, & Pack, 2007).…”
Section: Functional Considerationsmentioning
confidence: 84%